For h € ℝ and ϕ : ℝ2 → ℝ define Lhϕ: ℝ2 → ℝ by (Lhϕ)(x, y) = ϕ (x + h, y) + ϕ (x — h,y) — ϕ (x,y + h) — ϕ (x,y — h) for all (x,y) € ℝ2. The aim of the paper is to establish the following "stability" theorem concerning the functional equation
![](//static-cambridge-org.ezproxyberklee.flo.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0008439500004240/resource/name/S0008439500004240_eqn1.gif?pub-status=live)
if δ > 0, f : ℝ2 → ℝ and
![](//static-cambridge-org.ezproxyberklee.flo.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0008439500004240/resource/name/S0008439500004240_eqn2.gif?pub-status=live)
then there exists ɛ > 0 ami ϕ : ℝ2 → ℝ such that (Lhϕ)(x, y ) = 0 for all x, y,h ∊ ℝ and
![](//static-cambridge-org.ezproxyberklee.flo.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0008439500004240/resource/name/S0008439500004240_eqn3.gif?pub-status=live)